Did COVID-19 accelerate the green transition? An international assessment of fiscal spending measures to support low-carbon technologies - Aulie, Frida (OECD Science, Technology and Industry Policy Papers, 2023)
Fiscal spending policies adopted in the wake of the COVID-19 pandemic have been presented as a unique opportunity to "build back better" and re-ignite the economy while accelerating the transition to a low-carbon economy. This paper analyses 1 166 funding measures announced by 51 countries and the European Union in 2020-21 to support development and diffusion of low-carbon technologies. These measures - amounting to USD 1.29 trillion - can make an important contribution to filling the climate investment gap, particularly in emerging technologies such as carbon capture, usage and storage and green hydrogen. A modelling analysis suggests that they could have large impacts on greenhouse gas emissions and bring about significant co-benefits in terms of clean sectors' output growth and reductions in fossil fuel imports